Numerical experiments on the solution of Helmholtz equation in the case of domains of complicated boundary shape. - Sánchez Sarmiento, G.; Laura, P. A. A. (North Holland Publishing Co., 1979)
Fil: Sánchez Sarmiento, G. Comisión Nacional de Energía Atómica; Argentina